DORA nieuwsbrief : Dames Ondernemen Reizen Alleen. (Amsterdam : Stichting DORA, 1991)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijksRedactie : PB 14735, 1001 LE Amsterdam
Nederlands
Periodiek